Gross Hematuria following SARS-CoV-2 Vaccination - Maryam Sattari; Jourdan Mckinnis; Amir Kazory (Case Reports in Medicine)
In the setting of the rapid development of currently available vaccines for coronavirus disease of 2019 (COVID-19), little is known about their less frequent potential side effects. Raising the awareness of clinicians and front-line healthcare workers about the less well-known potential side effects of vaccination is important. We describe the self-limited occurrence of gross hematuria in two elderly men on a combination of aspirin and another antiplatelet or anticoagulant following their second dose of the Moderna COVID-19 vaccination. While the bleeding seems to be self-limited, the long-term course currently remains elusive.